Biochemical evidence for presynaptic and postsynaptic alpha-adrenoceptors in rat heart membranes: positive homotropic cooperativity of presynaptic binding. - Guicheney, P (1978)
In crude rat cardiac membrane preparations, [3H]dihydroergocryptine (3H-DHE) appears to bind to two classes of sites with limited capacity, differing in their specificities and their affinities. The first class of binding sites interacts preferentially with the postsynaptic alpha-adrenoceptor blocker ARC239, as can be expected for postsynaptic alpha-adrenoceptors. The binding of 3H-DHE to these receptors follows the law of mass action, with a high affinity for 3H-DHE (Kd 25 degrees C = 1.67 +/- 0.37 nM). Postsynaptic saturating levels of 3H-DHE are necessary to occupy the second class of binding sites. These sites exhibit a preferential affinity for presynaptic ligands such as clonidine and yohimbine, as would be expected for presynaptic alpha-adrenergic receptors. This presynaptic binding shows a markedly positive homotropic cooperativity (Hill n = 2.88) with initial and final apparent Kds of 23 and 0.83 nM, respectively. Free energy of interaction between sites is of the order of 2 kcal (8.36 kJ)/mol of sites. These characteristics provide a rational molecular basis for the functional role of presynaptic alpha-adrenoceptors that mediate the inhibition of norepinephrine release from nerve endings.